Analisis Kepuasan Petani terhadap Kinerja Kelompok Tani (Suatu Kasus Pada Petani Di Desa Binong Kecamatan Binong Kabupaten Subang) - Agi Dahtiar; Anggito Abimanyu (Paspalum: Jurnal Ilmiah Pertanian, 2023)
The purpose of this research is to assess how satisfied farmers are with the performance of farmer groups in Binong village, Binong sub-district, and how well those groups' performance parameters match farmers' expectations. A questionnaire was employed for this research. A total of 75 participants were sampled using a proportional stratified random method. Attribute seven, "organizing and carrying out the division of tasks among members according to mutual agreement," had the highest level of conformity between importance and performance among the performance attributes of farmer groups, at 91.60%, according to the study's findings. Improving the sustainability of productivity while also protecting natural resources and the environment ranks lowest among the four most important areas for development identified by the Cartesian diagram. a decline in efficiency. According to data from the Customer Satisfaction Index (CSI) measuring various aspects of farmer organizations' performance, the vast majority of farmers are happy with their services.